Pterostilbene, a Methoxylated Resveratrol Derivative, Efficiently Eradicates Planktonic, Biofilm, and Intracellular MRSA by Topical Application - Yang, Shih-Chun; Tseng, Chih-Hua; Wang, Pei-Wen; Lu, Po-Liang; Weng, Yi-Han; Yen, Feng-Lin; Fang, Jia-You (Frontiers in Microbiology, 2017)
Pterostilbene is a methoxylated derivative of resveratrol originated from natural sources. We investigated the antibacterial activity of pterostilbene against drug-resistant Staphylococcus aureus and the feasibility of using it to treat cutaneous bacteria. The antimicrobial effect was evaluated using an in vitro culture model and an in vivo mouse model of cutaneous infection. The minimum inhibitory concentration (MIC) assay demonstrated a superior biocidal activity of pterostilbene compared to resveratrol (8~16-fold) against methicillin-resistant S. aureus (MRSA) and clinically isolated vancomycin-resistant S. aureus (VRSA). Pterostilbene was found to reduce MRSA biofilm thickness from 18 to 10 μm as detected by confocal microscopy. Pterostilbene showed minimal toxicity to THP-1 cells and was readily engulfed by the macrophages, facilitating the eradication of intracellular MRSA. Pterostilbene exhibited increased skin absorption over resveratrol by 6-fold. Topical pterostilbene application improved the abscess formation produced by MRSA by reducing the bacterial burden and ameliorating the skin architecture. The potent anti-MRSA capability of pterostilbene was related to bacterial membrane leakage, chaperone protein downregulation, and ribosomal protein upregulation. This mechanism of action was different from that of resveratrol according to proteomic analysis and molecular docking. Pterostilbene has the potential to serve as a novel class of topically applied agents for treating MRSA infection in the skin while demonstrating less toxicity to mammalian cells.